Energy and macronutrients intake in an Italian infants cohort at 24 months of age. (20th October 2021) - Valdi, G; Moretti, V; Concina, F; Pani, P; Carletti, C; Ronfani, L; Parpinel, M
Abstract: Background: Dietary habits during infancy and early childhood could have short and long-term health effects and could influence future adults' dietary habits. Acting during this sensitive period of life could be crucial. In 2006 a prospective infants cohort study was established at the Maternal and Child Institute - Burlo Garofolo in Trieste, Italy (Trieste Infant Feeding Cohort - TIF cohort) to assess energy and nutrients intake during the first three years of infants' life. This nutritional analysis focused on dietary habits of infants at 24 months of age. Methods: Dietary data were collected using a 3-day dietary record (3-d DR) and data were analysed using a nutritional software containing the Italian Food Composition database and integrated with data from nutritional labels and literature. Energy and macronutrients intake were compared with the Italian Dietary Reference Values (DRV) and the WHO recommendation. Differences by sex were also assessed. Results: 3d-DR was filled for 157 infants. Available carbohydrates (CHO) and starch intakes were significantly significant higher in males (p < 0.05). The percentage contribution of CHO to total energy intake was in line with DRV (75.8% of infants within the reference interval (RI)) similarly 75.2% of infants are within the RI for fats. Proteins' contribution to energy intake, instead, was above the RI for 53.5% of infants over the RI and the daily protein intake was greater than the estimated DRV (median 43.9 g/d, IQR of 16.2 g/d vs median DRV 10.3 g/d, IQR 1.3 g/d). Conclusions: The results show a substantial adherence with recommendations for macronutrient intakes except for the excess protein intake. Elevated protein intake play a role in developing long-term health consequences and seems linked to overweight and obesity. Further evaluation of protein intake should be desirable. Key messages: Nutritional studies are essential tools to assess dietary habits in infants and allow to contribute of reference recommendations evolution. Macronutrients analysis, with a particular focus on proteins intake, can help to evaluate children' dietary patterns, to intercept and possibly correct unhealthy habits.